2019
DOI: 10.1001/jamadermatol.2018.4378
|View full text |Cite
|
Sign up to set email alerts
|

Expert-Level Diagnosis of Nonpigmented Skin Cancer by Combined Convolutional Neural Networks

Abstract: IMPORTANCE Convolutional neural networks (CNNs) achieve expert-level accuracy in the diagnosis of pigmented melanocytic lesions. However, the most common types of skin cancer are nonpigmented and nonmelanocytic, and are more difficult to diagnose. OBJECTIVE To compare the accuracy of a CNN-based classifier with that of physicians with different levels of experience. DESIGN, SETTING, AND PARTICIPANTS A CNN-based classification model was trained on 7895 dermoscopic and 5829 close-up images of lesions excised at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
143
1
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(163 citation statements)
references
References 45 publications
(61 reference statements)
1
143
1
7
Order By: Relevance
“…In contrast, determining the diagnosis of melanoma versus benign pigmented nevus is a simpler binary classification problem. In 2019, Tschandl et al [52] demonstrated that a combined CNN (cCNN) can classify dermoscopic and clinical images of nonpigmented lesions on par with experts, namely 95 human raters of whom 62 were board-certified dermatologists. The authors combined the outputs of two CNNs, one trained with dermoscopic images and the other with clinical images.…”
Section: Non-melanoma Skin Cancermentioning
confidence: 99%
“…In contrast, determining the diagnosis of melanoma versus benign pigmented nevus is a simpler binary classification problem. In 2019, Tschandl et al [52] demonstrated that a combined CNN (cCNN) can classify dermoscopic and clinical images of nonpigmented lesions on par with experts, namely 95 human raters of whom 62 were board-certified dermatologists. The authors combined the outputs of two CNNs, one trained with dermoscopic images and the other with clinical images.…”
Section: Non-melanoma Skin Cancermentioning
confidence: 99%
“…Another interesting application of DL is on predicting Alzheimer's disease approximately 6 years before the disease strikes, using PET brain scans (Ding et al, 2018). In dermatology, a few recent examples of DL showed higher accuracy than experts at diagnosing skin cancer (Esteva et al, 2017;Haenssle et al, 2018;Tschandl et al, 2019). In cardiology, a novel DL approach was implemented to automate diagnosis of acute ischemic infarction on CT (Beecy et al, 2018).…”
Section: State Interpretationcomparison To Populationmentioning
confidence: 99%
“…Several studies have now shown that CNNs trained on retrospective image data collected at a single time point are capable of classifying skin cancer with sensitivities and specificities equal or superior to that of dermatologists (Box 1), and clinicians with less experience gain most from AI support under experimental conditions . Hypomelanotic and acral melanoma can be more challenging to diagnose clinically, and this could potentially present a challenge for automated classification.…”
mentioning
confidence: 99%
“…Hypomelanotic and acral melanoma can be more challenging to diagnose clinically, and this could potentially present a challenge for automated classification. However, CNNs have achieved greater accuracy for hypopigmented and acral lesions in comparison with human experts, at least in silica . In addition to clinical images, CNNs have been applied to histopathological images of melanoma and benign naevi with promising results …”
mentioning
confidence: 99%